Linguistic development of students of language universities taking into account the cross-cultural aspect in teaching [Лингвистическое развитие студентов языковых вузов с учетом кросс-культурного аспекта в преподавании] (in Russian) - Иванченко, Андреянна Алексеевна; Лукашенко, И.Н.; Падоан, И.М.; Гава, Г.В.; Гусля, Л.В.; Іванченко, Андреянна Олексіївна; Ivanchenko, Andreyanna (Харьков, ХНУ им. В.Н. Каразина, 2002)
In this article it is written about the necessity of the culturality inserted at the beginning of Italian language study. It contributes to reduce psychological and linguistic shock as well as to increase the motivation and affectivity of studying language mastering. This status was conformed practically by means of specially organized teaching directed to the knowledge of the cultural heritage, peculiarity and specificity of the Italian nationality. В статье говорится о необходимости аккультурации еще в начале изучения итальянского языка, что способствует снижению психологического и лингвистического шока, а также повышению мотивации и эффективности усвоения изучаемого языка. Данное положение было подтверждено на практике путем специально организованного обучения, направленного на познание культурного наследия и особенностей итальянского этноса.
Keywords: linguistic development; psycho-linguistic shock; motivation and affectivity; Italian language studying; organized teaching; cultural heritage